Upaya Egaliter Terhadap Diskriminasi Perempuan Infertilitas Dalam Prespektif al-Qur’an (Studi Gender Pendekatan Teologi-Sintesis) - Muslihudin Muslihudin; Yulita Putri; Muhamad Fiqhussunnah Al Khoiron; Abid Nurhuda (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2023)
This research departs from the view that should not exist in society towards women who experience problems in producing offspring (infertility). The views of the majority of society give rise to injustice and discrimination, especially for women. Therefore, the purpose of this research is to work hard to change this injustice and form a constructive and contextual theology needed to realize a liberating understanding for women and men. This scientific study is a qualitative research using the method of literature study on the interpretation of the Qur'an, namely al-Mufradat fi Gharib al-Qur'an by al-Raghib al-Ashfahani and literature related to the theme. The approach used is the theological-synthetic approach. Namely trying to express the meaning of infertility in the book of interpretations al-Mufradat fi Gharib al-Qur'an which is brought together with scientific knowledge and the cultural context of society. The results of the study show that Egalitarian Efforts Against Discrimination against Infertility Women in the Perspective of the Koran is embodying the spirit of equality that upholds humanist values, and freedom and eliminates discrimination against infertile women in society because it is a manifestation of the interpretation of the Qur’an, science, and culture.